Life Energy By Symmetric Quartic Power Curves (Global Journal of Science Frontier Research, 2024)
Life of a living being is mathematically modelled as a Quartic Power Curve in the time Then we compute the Energy of Life of such an individual as a Quintic in the time More applications of this model to real life will follow in the future now just the basic mathematics is described in this brand-new paper
Keywords: quartic model; life modeling; energy of life; polynomial curve; lifespan analysis; growth and decline